Education and training policies for research integrity: Insights from a focus group study. (25th November 2021) - Labib, Krishma; Evans, Natalie; Roje, Rea; Kavouras, Panagiotis; Reyes Elizondo, Andrea; Kaltenbrunner, Wolfgang; Buljan, Ivan; Ravn, Tine; Widdershoven, Guy; Bouter, Lex; Charitidis, Costas; Sørensen, Mads P; et al.
Abstract: Education is important for fostering research integrity (RI). Although RI training is increasingly provided, there is little knowledge on how research stakeholders view institutional RI education and training policies. Following a constructivist approach, we present insights about research stakeholders' views and experiences regarding how research institutions can develop and implement RI education and training policies. We conducted thirty focus groups, engaging 147 participants in eight European countries. Using a mixed deductive-inductive thematic analysis, we identified five themes: (1) RI education should be available to all; (2) education and training approaches and goals should be tailored; (3) motivating trainees is essential; (4) both formal and informal educational formats are necessary; and (5) institutions should take into account various individual, institutional, and system-of-science factors when implementing RI education. Our findings suggest that institutions should make RI education attractive for all and tailor training to disciplinary-specific contexts.